WRITTEN WORLD : HOW LITERATURE SHAPES HISTORY - MARTIN PUCHNER (LONDON GRANTA, 2018)
The story of literature in sixteen acts, from Alexander the Great and the Iliad to ebooks and Harry Potter, this engaging book brings together remarkable people and surprising events to show how writing shaped cultures, religions, and the history of the world.
Keywords: LITERATURE-HISTORY; LITERATURE AND SOCIETY; BOOKS AND READING